Experimental Research and Instrument Design of Seepage Measurement in Rock and Soil Based on Heat Transfer - Wu, Xiushan; Cui, Jiamin; Tong, Renyuan; Li, Qing (Frontiers in Earth Science, 2022)
Seepage in the underground rock and soil is one of the main causes of geological disasters. Precursor information for geological disasters is provided by accurately measuring the seepage flow in rock and soil, so as to provide disaster warnings in time. This article analyzes the principle of seepage measurement in rock and soil based on heat transfer, deduces the relationship between the flow rate and temperature of the fluid with a seepage sensor, designs and manufactures an entire seepage measurement sensor, and designs a seepage measurement circuit. Finally, a set of portable geotechnical seepage measuring instruments is designed. An experimental platform is designed to realize seepage flow and temperature change experiments with the seepage sensor, it is proved that the sensor can effectively measure the seepage flow for different experimental samples, the measurement range is 0.06–0.160 ml/s. Based on the measured characteristic temperature of the seepage sensor, the calculated seepage flow is obtained, the relative error between the calculated value and the measured value is within 3%.